Collectivization generation : oral histories of a social revolution in Uzbekistan - Kamp, Marianne (2024)
"This book is a history of agricultural collectivization in Soviet Uzbekistan, but it is not focused on Party decisions. It is instead a history of everyday life that relies on voices of oral history respondents whom I call the collectivization generation. Born between the early 1900s and the early 1920s, the collectivization generation were rural youth who, willingly or unwillingly, participated in this transformation of agricultural life in the early 1930s as teens or young adults"-- Provided by publisher.
Inedible harvest -- Bosmachi stories -- Land reform -- Agitating for the kolkhoz -- Making quloqs -- Famine -- Working -- Orphans.
Includes bibliographical references (pages 231-282) and index.
Keywords: Collectivization of agriculture -- Social aspects -- Uzbekistan; Rural youth -- Uzbekistan -- Social conditions -- 20th century; Uzbekistan -- Social conditions -- 1917-1991